Hubungan Asupan Gizi Anak, Aktivitas Fisik Dan Pengetahuan Gizi Ibu Dengan Status Gizi Anak Usia Sekolah di UPT SDN 104244 Jati Sari Kecamatan Lubuk Pakam Jl. Inpres Desa Tg. Garbus I - Mayasari Sinaga; Mei Oktavia Sinurat; Zuraidah Nasution (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
School-age children are the age group of 6-12 years and an important period of growth and development, so adequate nutritional intake is needed to avoid nutritional problems. Children's nutritional intake that does not comply with the 2019 Nutritional Adequacy Intake and unhealthy physical activity patterns can disrupt energy balance and trigger nutritional problems. Mother's nutritional knowledge is important in determining the type and amount of food consumed by children so that the child's nutritional status is normal. The purpose of this study was to determine the relationship between children's nutritional intake, physical activity, and maternal nutritional knowledge with the nutritional status of school-age children at UPT SDN 104244 Jati Sari, Lubuk Pakam District, Jl. Inpres, Tg. Garbus I Village. This research was conducted at UPT SDN 104244 Jati Sari, Lubuk Pakam District from January 13 to January 20, 2025. This type of research is observational with a cross-sectional design. The population in this study were students in grades III to V who were selected by random sampling, with a sample of 57 people using the Slovin formula Data was collected through measurements of height and weight, a non-consecutive 3x24-hour food recall form, the Physical Activity Questionnaire for Children (PAQ-C) and maternal nutritional knowledge questionnaire. The statistical analysis employed was the Chi-square test. The research results indicate a significant relationship between children's nutritional intake (energy, carbohydrates, protein, fat, vitamins A, B6, E, C, iron and zinc) with p-value = 0.001, physical activity (p-value = 0.001), maternal nutritional knowledge (p-value = 0.001) and the nutritional status of school-age children.